Hormone receptor status and survival of medullary breast cancer patients - Aksoy, Asude; Odabas, Hatice; Kaya, Serap; Bozkurt, Oktay; Degirmenci, Mustafa; Topcu, Turkan O.; Gumus, Mahmut (Saudi Med J, 2017)
Objectives: To analyze the relationship between clinical features, hormonal receptor status, and survival in patients who were diagnosed with medullary breast cancer (MBC). Methods: Demographic characteristics, histopathological features, and survival statuses of 201 patients diagnosed with MBC between 1995 and 2015 were retrospectively recorded. Survival analyses were conducted with uniand multivariate cox regression analysis. Results: Median follow-up time was 54 (4-272) months. Median patient age at the time of diagnosis was 47 years old (26-90). Of the patients, 91.5% were triple negative. Five-year recurrence free survival time (RFS) rate was 87.4% and overalll survival (OS) rate 95.7%. For RFS, progesterone receptor (PR) negativity, atypical histopathological evaluation, absence of lymphovascular invasion, smaller tumor, lower nodal involvement were found to be favourable prognostic factors by univariate analysis (p<0.05). The PR negativity and smaller tumor were found to be favourable factors by univariate analysis (p<0.05). However, none of these factors were determined as significant independent prognostic factors for OS (p>0.05). Conclusion: Turkish MBC patients exhibited good prognosis, which was comparable with survival outcomes achieved in the literature. The PR negativity was related to a better RFS and OS rates.
Keywords: Clinicopathological Characteristics; Spontaneous Regression; Carcinoma; Heterogeneity; Inflammation